Repercussões da dança folclórica alemã sob a perspectiva de pessoas com deficiência e demais participantes - Silva, Bruna Poliana (2022)
German Folk Dance is a group dance, the dancers being gathered in circles, lines or in pairs. Choreographies represent different situations that relate to German culture, so as to preserve the richness of this culture by the means of dance. Among the participants, one finds some disabled persons. Up to now, there have been no identified studies on German Folk Dance in regard to its impact on the lives of disabled persons. The general objective of this study was to understand the influence of German Folk Dance in the life of disabled persons. The specific objectives were: a) to analyse the meaning of German Folk Dance in the life of disabled persons; b) to identify the impressions of family and dance group members in regard to the participation of disabled persons; and c) to investigate the possibilities and limits of the teaching of German Folk Dance in the perspective of group coordinators. The research was developed in a qualitative exploratory approach as a case study. As an instrument for data collection, the researched has used sociodemographic questionnaires and semi structured interviews. Due to participants’ location, data collection was carried out online, via the open applications Google Forms and Google Meet. Interviews were manually transcribed. Participants of the data collection were 19 coordinators, 10 group members with disabilities, 10 family members, and 10 fellow group members. Data was treated by thematic analysis and results have been presented in three parts: a) characteristic description of participants; b) description and discussion of the 10 cases; c) thematic analysis in three sections. First, on the meaning of German folk dance for people with disabilities, about which participants have mentioned terms such as “fun”, “presentation” and “attire”. Second comes the impressions of friends and family, who have mentioned “motivation”, “inclusion”, “autonomy”, and “learning about a new culture”. In regard to the possibilities of the teaching of German Folk Dance, coordinators have mentioned benefits in social, physical, cultural and cognitive aspects; in regard to its limits, they have mentioned familiar aid, coordinator training, and attitudinal barriers. One can conclude that German Folk Dance allows the participation of both people with and without disabilities, preserving popular traditions and a felling of togetherness among all participants, which has a positive impact in their lives.